2010
DOI: 10.1088/1748-9326/5/1/014015
|View full text |Cite
|
Sign up to set email alerts
|

Supply-chain environmental effects of wastewater utilities

Abstract: This letter describes a comprehensive modeling framework and the Wastewater-Energy Sustainability Tool (WWEST) designed for conducting hybrid life-cycle assessments of the wastewater collection, treatment, and discharge infrastructure in the United States. Results from a case study treatment plant which produces electricity using methane offgas are discussed. The case study system supplements influent with 'high-strength organic waste' to augment electricity production. The system balance is 55 kg of greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 17 publications
0
39
0
2
Order By: Relevance
“…Further investigation of the environmental externalities associated with both supply-and demand-side water projects can provide decision-makers with a more complete view of the full environmental costs of water management. For example, reduction of water demand volume from water efficiency technology adoption is associated with direct impacts on drinking water distribution and wastewater treatment plant operations (Stokes and Horvath, 2010, 2009Alvarez-Gaitan et al, 2014;Lundie et al, 2004;Short et al, 2014). Indirect impacts from avoided importation, desalination, and recycling supply-side projects, which can be associated with higher energy-use intensity than are traditional water provisions, also must be estimated.…”
Section: Study Limitations and Recommendations For Future Workmentioning
confidence: 99%
“…Further investigation of the environmental externalities associated with both supply-and demand-side water projects can provide decision-makers with a more complete view of the full environmental costs of water management. For example, reduction of water demand volume from water efficiency technology adoption is associated with direct impacts on drinking water distribution and wastewater treatment plant operations (Stokes and Horvath, 2010, 2009Alvarez-Gaitan et al, 2014;Lundie et al, 2004;Short et al, 2014). Indirect impacts from avoided importation, desalination, and recycling supply-side projects, which can be associated with higher energy-use intensity than are traditional water provisions, also must be estimated.…”
Section: Study Limitations and Recommendations For Future Workmentioning
confidence: 99%
“…Both digesting organic waste and improving landfill gas capture rates can be done using already existing infrastructure. Conventional wastewater treatment plants already have anaerobic digesters for liquid wastes (Stokes and Horvath 2010), and co-digestion of liquid and solid wastes has been shown to increase methane generation (Edelmann 2000;Sosnowski et al 2008), though the mixing of liquid and solid wastes brings on added risks of pathogens, and can limit the possibilities for land application of the waste (Murray et al 2008). …”
Section: Counting Biogenic Carbon Emissionsmentioning
confidence: 99%
“…These studies have identified energy consumption, chemical manufacturing, and sludge handling and disposal to be the main contributors to environmental emissions . LCA results for a case study of a wastewater treatment plant that produces electricity using methane gas obtained from the biological treatment of high‐strength organic wastewater were developed using the WWEST model . The results of the case study showed that the treatment phase dominated the results, contributing 63–106% to each emission category .…”
Section: Introductionmentioning
confidence: 99%
“…LCA results for a case study of a wastewater treatment plant that produces electricity using methane gas obtained from the biological treatment of high‐strength organic wastewater were developed using the WWEST model . The results of the case study showed that the treatment phase dominated the results, contributing 63–106% to each emission category . Another LCA study for municipal wastewater reclamation and reuse alternatives showed that tertiary treatment contributed to additional environmental impacts, but the benefit of reusing water for industrial and commercial purposes helps preserve freshwater .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation